PERENCANAAN PERKERASAN KAKU (RIGID PAVEMENT) PADA RUAS JALAN STA 0+1 KM KECAMATAN BINANGUN KABUPATEN BLITAR JAWA TIMUR - Brunosius, Brunosius; arifianto, andi kristafi; Primasworo, Rifky Aldila (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
The highway is a target trajectory of transportation that serves to reach from one place to another. Therefore, to improve and expedite the flow of traffic on roads Binangun, District Binangun, Blitar in East Java requires good planning in order to obtain good results and also economically. This study aims to plot thick rigid pavement on roads Binangun with melekukan survey include traffic data on average daily, know the condition of the road, and the measurement path. This plan is intended to plan a road thick rigid pavement on roads Binangun. The method used in the planning of this road is rigid pavement using NAASRA (National Association of Australian State Road Authorities). Data analysis methods used, among others, are planning a thick slab of concrete, reinforcement planning, planning connection (Dowel and Tie Bar). Expenses for rigid pavement construction planning amounted to 60,243,947.1 kg/m3 of load for flexible pavement construction planning amounted to 48,009,707.1 kg/m3 . The number of vehicles according the survey data over the age of plans based on the total fatigue approaching or equal to 100 % . The importance of the rigid pavement thickness to be used on roads Binangun Blitar District of Binangun are 180 mm = 18 cm. Keywords: Rigid Pavement, NAASRA